Bio-Monitoring of Aquatic Environment: Hematological and Biochemical Changes in Grass Carp due to Toxicity of Emamectin Benzoate, Acetochlor, and Topsin-m - Khan Dil Badshah; Bilal Riaz; Rameen Ejiz; Ashfaq A. Khan; Kamran Mehdi; Saqib Khan; Sania Riaz; Kamil Ahmad; Naseer Ahmed (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract